Chinese Lexical Semantics 16th Workshop, CLSW 2015, Beijing, China, May 9-11, 2015, Revised Selected Papers - Lu, Qin.; Gao, Hong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-workshop proceedings of the 16th Chinese Lexical Semantics Workshop, CLSW 2015, held in Beijing, China, in May 2015. The 64 regular and 4 short papers included in this volume were carefully reviewed and selected from 248 submissions. They are organized in topical sections named: lexical semantics; lexical resources; lexicology; natural language processing and applications; and syntax.
Lexical semantics -- Lexical resources -- Lexicology -- Natural language processing and applications -- Syntax.
Keywords: Artificial intelligence; Natural language processing (Computer science).; Chinese language; Mathematical logic; Information storage and retrieval; Artificial Intelligence; Natural Language Processing (NLP).; Chinese; Mathematical Logic and Formal Languages; Information Storage and Retrieval